Dynamic Stabilization Adjacent to Fusion versus Posterior Lumbar Interbody Fusion for the Treatment of Lumbar Degenerative Disease: A Meta-Analysis. (20th May 2020) - Sun, Xiangyao; Chen, Zhaoxiong; Sun, Siyuan; Wang, Wei; Zhang, Tongtong; Kong, Chao; Lu, Shibao
Abstract : This study evaluated differences in outcome variables between dynamic stabilization adjacent to fusion (DATF) and posterior lumbar interbody fusion (PLIF) for the treatment of lumbar degenerative disease. A systematic review of PubMed, EMBASE, and Cochrane was performed. The variables of interest included clinical adjacent segment pathologies (CASPs), radiological adjacent segment pathologies (RASPs), lumbar lordosis (LL), visual analogue scale (VAS) of back (VAS-B) and leg (VAS-L), Oswestry disability index (ODI), Japanese Orthopaedic Association (JOA) score, duration of surgery (DS), estimated blood loss (EBL), complications, and reoperation rate. Nine articles identified as meeting all of the inclusion criteria. DATF was better than PLIF in proximal RASP, CASP, and ODI during 3 months follow-up, VAS-L. However, no significant difference between DATF and PLIF was found in distal RASP, LL, JOA score, VAS-B, ODI after 3 months follow-up, complication rates, and reoperation rate. These further confirmed that DATF could decrease the proximal ASP both symptomatically and radiographically as compared to fusion group; however, the influence of DATF on functional outcome was similar with PLIF. The differences between hybrid surgery and topping-off technique were located in DS and EBL in comparison with PLIF. Our study confirmed that DATF could decrease the proximal ASP both symptomatically and radiographically as compared to the fusion group; however, the influence of DATF on functional outcome was similar with PLIF. The difference between hybrid surgery and topping-off technique was not significant in treatment outcomes.